A New Type of Renal Cancer—Tubulocystic Carcinoma of the Kidney: A Review of the Literature. (June 2014) - Bhullar, Jasneet Singh; Varshney, Neha; Bhullar, Amanpreet Kaur; Mittal, Vijay K.
In 2004, A new peculiar subtype of renal cell carcinoma, which later received the name of tubulocystic carcinoma (TCC-RC), was recognized. Though the tumor has distinct macroscopic, microscopic and immunohistochemical features, the tumor was previously considered to have some similarities to various other renal cancers. We did an extensive review of literature using PubMed and CrossRef, which yielded more than 80 cases reported from various parts of the world. We evaluated the epidemiology, tumor presentations, pathological characteristics, treatment, and outcome of TCC-RC.